NAFKAH ANAK TERHADAP ORANG TUA MENURUT HUKUM ISLAM - Emi Yasir; Marsuni Marsuni; Zulkarnaini Zulkarnaini (SYARIAH: Journal of Islamic Law, 2023)
specifically from the laws and regulations in Indonesia and also from the perspective of Islamic law. As a result, many parents are displaced without any sense of care from their children. Even though parents are people who must be respected for caring for and raising their children. The study aims to find out and analyze the understanding of the postulate of children's livelihood towards parents in fiqh and the explanation of syar'i related to children's livelihood to parents in Islamic law. The research method used is a qualitative research method. Data are obtained through the study of documentation and literature of materials contained in the library. Data analysis is carried out qualitatively on the basis of data obtained from the library. The results showed that none of the Quranic and Sunnah arguments stated unequivocally the obligation of children to provide for their parents, but the scholars expressed the obligation to provide a husband's livelihood to his wife. Giving a living to a wife is mandatory, so giving a living to parents is also mandatory, because parents have begun to age which requires attention from children to nurture the soul (hifáº“ al-nafs) as part of the islamic law. The child's livelihood towards parents is due to the existence of the closest and inseparable kinship between the child and the parents.